An Efficient Solvothermal Method for One‐Pot Batch Simultaneous Synthesis of OZPMs and DHPMs. Issue 15 (14th April 2023) - Chen, Dan; Pan, Xin‐Guang; An, Yan; Zheng, Lu; Liu, Yu; Wang, Shi‐Fan
Abstract: An efficient solvothermal method for one pot batch simultaneous synthesis of oxazolopyrimidines and dihydropyrimidinones has been developed in a small amount of lactic acid without any additional catalysts and additives for the first time. Ten oxazolopyrimidines and nine novel dihydropyrimidinones were simultaneously synthesized by the condensation of 1, 3‐dicarbonyl compounds, aromatic aldehydes and β‐hydroxyethylurea in the solvothermal reactors. All products were obtained in high yields and characterized by IR, 1 H NMR, 13 C NMR, and HR‐MS. Further, the structure of oxazolopyrimidine has been undoubtedly identified with the means of single crystal X‐ray diffraction. Abstract : An efficient solvothermal method for one pot batch simultaneous synthesis of Oxazolopyrimidines and dihydropyrimidinones has been developed in a small amount of lactic acid without any additional catalysts and additives for the first time.